2011
DOI: 10.3109/13651501.2011.572168
|View full text |Cite
|
Sign up to set email alerts
|

Anger expression and suppression among patients with essential hypertension

Abstract: Considering the fact that trait anger and anger suppression is more prevalent among people with hypertension than healthy individuals, it seems suitable to provide education concerning anger management and emotional expression for these patients with regard to the anger issue which is a psychosomatic aspect of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 7 publications
2
12
0
3
Order By: Relevance
“…Also, in older adults, depression and lowered quality of life were positively correlated with each other [6,7]. A comparison of the anger of healthy individuals and that of patients indicated that the level of anger in patients suffering from conditions including stroke, coronary heart disease and hypertension was higher than that of healthy individuals [14,15], consistent with prior studies that also showed that anger was closely related with physical health. In studies that focused on nurses, it was shown that the anger expression style was related to physical and psychological health status [16,17] and the anger expression style was found to have an effect on the work environment, in areas such as job satisfaction, organizational commitment, and organizational performance [1].…”
Section: Introductionsupporting
confidence: 80%
“…Also, in older adults, depression and lowered quality of life were positively correlated with each other [6,7]. A comparison of the anger of healthy individuals and that of patients indicated that the level of anger in patients suffering from conditions including stroke, coronary heart disease and hypertension was higher than that of healthy individuals [14,15], consistent with prior studies that also showed that anger was closely related with physical health. In studies that focused on nurses, it was shown that the anger expression style was related to physical and psychological health status [16,17] and the anger expression style was found to have an effect on the work environment, in areas such as job satisfaction, organizational commitment, and organizational performance [1].…”
Section: Introductionsupporting
confidence: 80%
“…All studies used the STAXI and all but 3 reported a reliable method of blood pressure measurement. 66,67,74 Thus, it can be concluded that most studies were methodologically sound with respect to measurement techniques. Trait anger subscales and their relationship to blood pressure have only been evaluated in 1 study that examined war veterans.…”
Section: Trait Angermentioning
confidence: 99%
“…All 5 studies reporting positive results included normotensive subjects along with either white-coat hypertensives, 72 mild hypertensives 68,73 or hypertensives. 66,67 Together, this information outlines the diversity and significant number of studies that have examined relations between trait anger and blood pressure.…”
Section: Trait Anger: Cross-sectional Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Já Lipp (2005), a partir de pesquisas, concluiu que, independente do estilo de expressão da raiva ser para fora ou para dentro, quando é muito frequente, se mostra associado a aumentos da reatividade cardiovascular. Em relação à hipertensão, a tendência a suprimir constantemente a raiva, direcionando-a para dentro, vem sendo associada positivamente a essa doença (Hosseini, Mokhberi, Mohammadpour, Mehrabianfard, & Lashak, 2011;Ohira, 2010).…”
unclassified